(untitled) (REMUNOM, 2026)
Gender-based violence and feminicide represent persistent and complex social problems that challenge contemporary legal institutions and public policies. In Brazil, the confrontation of violence against women gained greater relevance with the creation of specific legal instruments aimed at protecting victims and holding aggressors accountable. In this context, the present study aims to analyze the limits and possibilities of the Maria da Penha Law in protecting women’s lives, considering recent scientific literature on domestic violence and feminicide. The research is characterized as a narrative literature review, based on the analysis of recent academic studies that discuss the effectiveness of public policies and legal mechanisms designed to address violence against women. The results indicate that the Maria da Penha Law represents an important advancement in the protection of women in situations of violence, particularly through the creation of urgent protective measures and the strengthening of the institutional network to combat domestic violence. However, the literature analyzed also highlights that the effectiveness of the legislation depends on the articulation between different public institutions, the expansion of preventive policies, and the strengthening of support services for victims. It is concluded that although Brazilian legislation represents a significant legal advancement, addressing gender-based violence requires integrated actions involving legal instruments, public policies, and social transformations aimed at promoting gender equality.